2006
DOI: 10.1159/000096176
|View full text |Cite
|
Sign up to set email alerts
|

Is 44-Hour Better than 24-Hour Ambulatory Blood Pressure Monitoring in Hemodialysis?

Abstract: The aim of this study is to evaluate if hemodialysis (HD) patients with similar blood pressure (BP) in the whole inter-HD period could have different target organ lesions and survival if the behavior of BP differs from the first to the second day of the inter-HD period. The present study compares 44-hour ambulatory BP monitoring (ABPM) patterns in 45 HD patients. Three BP patterns emerged: group A (n = 15) had similar BPs throughout (138 ± 11/88 ± 12 in the first 22 h vs. 140 ± 11/87 ± 12 mm Hg in the second 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…There seems to be a majority of dose-increases in the placebo group, which might explain the reduction in BP seen in placebo group. In hemodialysis patients BP is shown to increase in the inter-dialysis period [33]. Since BP is dependent on volume status, an improvement of volemic state might explain the reduction in BP.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be a majority of dose-increases in the placebo group, which might explain the reduction in BP seen in placebo group. In hemodialysis patients BP is shown to increase in the inter-dialysis period [33]. Since BP is dependent on volume status, an improvement of volemic state might explain the reduction in BP.…”
Section: Discussionmentioning
confidence: 99%
“…45 In particular, the effects of a reduced IWG on blood pressure should be examined via 24-h or 48-h blood pressure measurement in order to obtain a more exact evaluation of blood pressure characteristics 46 and to interpret possible differences in the survival rate. 47 Combined with regular medical and custodial care, TBWM is a feasible method to optimize the IWG and to reducte UFR at dialysis. Interventions by phone and instruction during dialyses can be planned easily.…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al. considered that HD patients should be subjected to 44‐h ABPM, and concluded that the increase in BP in the second half of the interdialytic period of 44‐h ABPM is of pathophysiological and prognostic importance regardless of the absolute mean BP value (3). In this study, no statistical significance was found for ABPM in the first 22 h, but mortality was found to be statistically significant in the second half of ABPM, as shown by the Cox hazard model (3).…”
Section: Discussionmentioning
confidence: 99%
“…The best timing and method of blood pressure (BP) measurement in HD patients are still uncertain. The BP variability and extreme changes of the volemic state make it difficult to obtain truly representative values of BP in HD patients if these are based only on isolated BP measurements in a dialysis center (3). There are many differences in terms of BP measurement techniques, the timing of measurements in relation to the HD session, and reliance on the use of home BP measurements or ambulatory blood pressure (ABP) monitoring (ABPM) (4).…”
mentioning
confidence: 99%